Le risque "Eau douce" : analyse des sites en Baie des Veys et du Bassin de Marennes Oléron - Soletchnik, Patrick; Ropert, Michel; Grangere, Karine; Munaron, Dominique; Struski, C. (Présentation Séminaire MOREST, Caen, 14-26 novembre 2004, 2004)
The role of freshwater is more difficult to comprehend. It might act as a detrital organic matter "vector" (during floods) or an anthropic waste "vector" (toxic molecules from agriculture or other industries; nutritive salts from leaching.). Its effect has been demonstrated in the Bay of Veys (Ropert and Kopp, 2000; Misko, 2003), and especially its intense but transient action, presenting high freshenings, as recorded by high-frequency multiparameter probes since 1996 [15]. On this oyster culture site, mortality could then result from osmotic shocks. The "mortality-flow" relationship, demonstrated in 2003 in the Bay of Veys (Misko 2003), has to be specified. It is found in a more sustained way in the Marennes Oléron Bay (R2 = 0.40). This result also needs to be specified. However, the freshwater factor has to be taken into account in the combination of causes leading to mortality in this basin. On the other hand, the lowest salinities (24-25) recorded with the high-frequency probes correspond to those of the dilution model. On the site of Auray, this information cannot lead to any conclusion about the influence of freshwater inputs on mortality. Multivaried analysis (ACP) conducted from a database matching mortality and environmental data on a total of 11 oyster culture sites shows that pluviometry affects the mortality rate of the 2-year-old oysters. In 2002, high mortality levels for adult oysters in the Bay of Veys were already linked with high autumn and winter pluviometry rates (Ropert and Kopp, 2000). The ACP analysis conducted on the Channel coast (Baie des Vey, Cancal, Paimpol, Morlaix, [13]), confirm this result. Finally, a "rough" typological study of the oyster culture sites shows that the volume of the input on those different sites, from catchment areas or river plumes, cannot predict, alone, the mortality rate of the C. gigas on those sites. As a conclusion, one has to search for other causes, independent or associated to the freshwater risk, on those sensitive sites. Le rôle de l'eau douce est ...